Combining diabetic foot and retinopathy screening: A step in the right direction? – a feasibility study. (July 2020) - Lewis, Jane EA; Morris, Keith; Powell, Thomas; Thomas, Rebecca L; Owens, David R
Objectives: Peripheral artery disease is a major cardiovascular disease affecting more than 200 million people globally and up to 4 times more frequent in the diabetic population. It can lead to lower extremity amputations or revascularisation and is associated with an increased risk of myocardial infarction, stroke and early mortality. This novel cross-sectional study aimed to explore the feasibility and acceptability of incorporating diabetic foot screening at routine diabetic retinopathy screening appointments. Methods: Participants underwent foot screening during the interval between pupil dilatation and retinal photography as part of the eye screening procedure. Lower limb arterial assessment included ankle brachial index, pulse volume waveform and protective light touch sensation. Results: Of 364 participants invited, 88% (n = 321) met the inclusion criteria. About 26.4% (n = 86) had asymptomatic peripheral artery disease and 3% (n = 10) had peripheral sensory neuropathy. Binary logistical regression analysis identified age (p < 0.005), existing coronary heart disease (p < 0.005) and gender (p = 0.03) as predictors of peripheral artery disease. Conclusion: Incorporating foot examination during eye screening appointments is feasible and was well received by participants and staff alike. Undiagnosed early peripheral artery disease was evident in a third of the study population emphasising the benefit of introducing foot surveillance into eye screening appointments for the early identification of lower limb arterial disease and peripheral sensory neuropathy.